Annual Plan 1995-96 - Planning Commission (Planning Commission, 1995)
The Eighth Five Year Plan (1992-97) was launched in the backdrop of a severe macroeconomic crisis. The crisis manifested itself in serious imbalances especially in the fiscal and the external sectors of the economy. These imbalances had been building up through the decade of the 1980s. In the absence of adequate corrective measures the problems became acute by early 1991.
Government of India Planning Commission
Government of India Planning Commission